Circles of influence: An analysis of charter school location and racial patterns at varying geographic scales - Gulosino, Charisse; dEntremont, Chad (Education Policy Analysis Archives, 2011)
This paper uses Geographic Information Systems (GIS) and dynamic mapping to examine student enrollments in New Jersey charter schools. Consistent with previous research, we find evidence of increased racial segregation. Greater percentages of African-Americans attend charter schools than reside in surrounding areas. We add to the existing charter school literature by more fully considering the importance of charter school supply and examining student enrollments across three geographic scales: school districts, census tracts and block groups. We demonstrate that racial segregation is most severe within charter schools’ immediate neighborhoods (i.e. block groups), suggesting that analyses comparing charter schools to larger school districts or nearby public schools may misrepresent student sorting. This finding appears to result from the tendency of charter schools in New Jersey to cluster just outside predominately African-American neighborhoods, encircling the residential locations of the students they are most likely to enroll.